Investigation of step electric drive as a control system for double-split hydrostatic mechanical transmissions - Самородов, Вадим Борисович; Митцель, Николай Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
The research deals with developing the control unit for variable displacement axial-piston pump with a hydromechanical control in the test bed of double-split hydrostatic mechanical transmission. Step electric drive was used as an actuator for controlling the hydraulic pump. During the study, static modes, as well as acceleration and deceleration processes of the tractor were simulated. As a result, high positioning accuracy of the hydraulic pump swash plate, regardless of speed and load on the output shaft was observed, and developed software has allowed to reproduce linear and nonlinear control laws. The relationship between the braking torque, applied to the output shaft, and a step change in its speed was revealed. Step electric drive in combination with the hydromechanical control of positive-displacement hydraulic machine can serve low-cost alternative to the electric proportional control. The designed stand is reconfigurable, which allows to perform a number of studies for the hydrostatic transmissions with a differential "at the output" and "at the input" and has the potential for further improvements.